Functional Assessment of Corticospinal System Excitability in Karate Athletes. - Fiorenzo Moscatelli; Giovanni Messina; Anna Valenzano; Vincenzo Monda; Andrea Viggiano; Antonietta Messina; Annamaria Petito; Antonio Ivano Triggiani; Michela Anna Pia Ciliberti; Marcellino Monda; Laura Capranica; Giuseppe Cibelli (PLoS ONE, 2016)
Objectives To investigate the involvement of the primary motor cortex (M1) in the coordination performance of karate athletes through transcranial magnetic stimulation (TMS). Methods Thirteen right-handed male karate athletes (25.0±5.0 years) and 13 matched non-athlete controls (26.7±6.2 years) were enrolled. A single-pulse TMS was applied using a figure-eight coil stimulator. Resting motor threshold (rMT) was determined. Surface electromyography was recorded from the first dorsal interosseous muscle. Motor evoked potential (MEP) latencies and amplitudes at rMT, 110%, and 120% of rMT were considered. Functional assessment of the coordination performance was assessed by in-phase (IP) and anti-phase (AP) homolateral hand and foot coordination tasks performed at 80, 120, and 180 bpm. Results Compared to controls, athletes showed lower rMT (p<0.01), shorter MEP latency (p<0.01) and higher MEP amplitude (p<0.01), with a significant correlation (r = 0.50, p<0.01) between rMT and MEP latency. Coordination decreased with increasing velocity, and better IP performances emerged compared to AP ones (p<0.001). In general, a high correlation between rMT and coordination tasks was found for both IP and AP conditions. Conclusion With respect to controls, karate athletes present a higher corticospinal excitability indicating the presence of an activity-dependent alteration in the balance and interactions between inhibitory and facilitatory circuits determining the final output from the M1. Furthermore, the high correlation between corticospinal excitability and coordination performance could support sport-specific neurophysiological arrangements.